2018
DOI: 10.1093/schbul/sby018.864
|View full text |Cite
|
Sign up to set email alerts
|

S77. Jumping to Conclusions and Facial Emotion Recognition Impairment in First Episode Psychosis Across Europe

Abstract: BackgroundJumping to conclusions (JTC) is a well-established reasoning and data gathering bias found in patients with psychosis even at illness onset (First Episode Psychosis, FEP). Preliminary work in this field focused primarily on the association with delusions, although jumping to conclusions has also been found in non-deluded schizophrenia patients after remission, and in individual with at risk mental state.Moreover, psychotic patients tend to show impairments in social cognition, struggling in identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…That is, those people who have the JTC bias do not necessarily interpret the mental states of others more poorly than people who do not JTC. Our findings are consistent with previous findings by Woodward et al 32 . Using factor analysis, these authors found that JTC loaded in a different neurocognitive factor than ToM.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…That is, those people who have the JTC bias do not necessarily interpret the mental states of others more poorly than people who do not JTC. Our findings are consistent with previous findings by Woodward et al 32 . Using factor analysis, these authors found that JTC loaded in a different neurocognitive factor than ToM.…”
Section: Discussionsupporting
confidence: 94%
“…These results highlight the need for improving reasoning judgments that are involved in ER in people with FEP. The results are consistent with the previous findings by Tripoli et al 31,32 where it was observed that patients with FEP who displayed JTC recognised worse emotions globally compared with controls, which is especially important because few psychological treatments intervene in both constructs 36 . In this line, psychological interventions such as metacognitive training for psychosis (MCT) would be recommended, because it works with specific modules about ER and the importance of making judgments based on the search of sufficient evidence to do that 37,38 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation